"Knowledge I seek because culture doesn't work anymore ... It doesn't work, death comes": the experiences of third-generation female caregivers (gogos) in South Africa discussing sex, sexuality and HIV and AIDS with children in their care - Jane E. Simmonds; Charles D. H. Parry; Fareed Abdullah; Nadine Harker Burnhams; Nicola Christofides (BMC, 2021)
Abstract Background Sexual reproductive health communication between parents and children has been shown to promote safer sexual choices. In many South African households, third-generation female caregivers, often grandmothers or other older females, locally known as gogos, are primary caregivers of children due to parents being deceased or absent. Subsequently, the responsibility of talking about sex and related issues has shifted to these gogos. This study explored the experiences of gogos living in Alexandra, Johannesburg on talking about sex, sexuality and HIV and AIDS with children aged 10-18 years that are in their care. Methods Ten primary caregivers were purposively selected. Data were collected through in-depth individual interviews. Thematic analysis was performed and inductive codes and themes identified. Results All gogos selected found it difficult to discuss sex, sexuality and HIV and AIDS due to culture and traditional values impacting on personal experiences as well as generation and gender barriers. Perceived low self-efficacy due to low levels of knowledge and limited skills in speaking about sex, sexuality and HIV and AIDS also contributed to low levels of sexual reproductive health communication. Conclusions This study highlights the need for interventions that focus on improving gogos' knowledge about sexual reproductive health in addition to providing them with the skills to talk about sex, sexuality and HIV and AIDS with children in their care.